The effect of unemployment, arrears and negative equity on consumption: Ireland in 2009/10 - Petra Gerlach-Kristen (The Economic and Social Research Institute (ESRI), 2013)
Since the onset of the financial crisis, income and consumption have fallen sharply in Ireland, particularly for young households. This paper shows that young households are more likely than older ones to be exposed to unemployment, arrears and negative equity. These may give rise to credit constraints and buffer-stock savings. Savings may be built up not only to finance future consumption, but also to deleverage, since high indebtedness makes the access to additional credit more difficult. We show that the permanent income hypothesis, which posits that consumption should evolve more smoothly than actual income, apparently fails to hold for households in negative equity, at risk thereof and at risk of unemployment. This may have caused much of the decline in aggregate consumption during the crisis.
Keywords: 330; Credit constraints; Ireland; Household Budget Survey